Planet City - Young, Liam (Architecture Image Studies, 2021)
Planet City is an urgent examination of the productive potential of extreme densification in an imagined future where ten billion people surrender the rest of the planet to a global wilderness. In a vision that runs counter to our current world, the project describes a radical reversal of planetary sprawl, where humans retreat from our vast network of cities and supply chains into one hyper-dense metropolis. Not a techno-utopian fantasy, this work of critical architecture and speculative fiction is grounded in statistical analysis, research, and traditional knowledge. This is essay has been developed from the transcript of the Planet City TED Talk delivered August 2021, it is based on a project that was the subject of a book Planet City published by Idea Books in 2020 and an accompanying film.